Diagnostic Utility of Microarray Testing in Pregnancy Loss. Issue 1 (January 2016) - Rosenfeld, J. A.; Tucker, M. E.; Escobar, L. F.; Neill, N. J.; Torchia, B. S.; McDaniel, L. D.; Schultz, R. A.; Chong, K.; Chitayat, D.
Abstract : Obstet Gynecol Surv 2016;71(1):15–16 Miscarriage is associated with 10% to 15% of all recognized pregnancies in the United States, and stillbirth occurs in approximately 1 in 165 births. Approximately 50% of recognized first-trimester miscarriages and 6% to 17% of stillbirths are chromosomally abnormal; therefore, diagnosis of a chromosomal abnormality as a cause of pregnancy loss provides important information for recurrence-risk counseling and helps identify familial chromosomal rearrangements.